Visualization representation benefits of pre-requirement specification tractability - Altaf, Sohaib; Shah, Asadullah; Imtiaz, Najma; Shah, Abdul Salaam; Ahmed, Syed Faiz (Science Publishing Corporation Inc., 2018)
Representation of Pre-RST information is very useful using visualization elements for realization of benefits of requirements tractability This improves the practitioners motivation to maintain Pre-RST information during life cycle processes. Few researchers proposed visualization for post-RST due to which many benefits of requirements tractability cannot be realized. This paper proposed an important visualization representing Pre-RST information that demonstrate various benefits of requirements tractability. In order to evaluate empirically an experiment is conducted and textual representation of tractability information is obtained. In order to strengthen our claim a survey is conducted to compare textual representation of tractability information with proposed visualization and results are compiled.